A new technique for environment identification in impulsive radio systems. (1st January 2012) - Mucchi, Lorenzo; Landi, Tommaso
Current wireless communication systems strongly need to know whether a line-of-sight (LOS) or non-LOS (NLOS) path is present between transmitter and receiver. The next generation wireless communication and localisation systems will require a more accurate environment identification in order to ensure a given level of QoS. In this paper we introduce a new environment identification technique which is able to identify not only the LOS/NLOS condition but also the typology of environment in which the transmitter and receiver operate: this allows both a more accurate localisation of all the users and a proper configuration of the receiver to best adapt to the propagation (cognitive approach) or network (cooperative approach) conditions. Unlike the techniques previously discussed in the literature, the one herein proposed does not require any estimation (ex. of channel parameters), while it is only based on a statistical analysis of the raw received UWB probe signal.